Does embryo quality at transfer affect obstetric outcomes and placental findings?. Issue 5 (9th March 2023) - Ganer Herman, Hadas; Volodarsky-Perel, Alexander; Ton Nu, Tuyet Nhung; Machado-Gedeon, Alexandre; Cui, Yiming; Shaul, Jonathan; Dahan, Michael H
Abstract: STUDY QUESTION: Do obstetric outcomes and placental findings in pregnancies conceived with IVF vary according to embryo quality? SUMMARY ANSWER: Pregnancies following the transfer of lower-quality embryos were associated with a higher rate of low-lying placentas and several adverse placental lesions. WHAT IS KNOWN ALREADY: A few studies have shown reduced pregnancy and live births rates with poor-quality embryo transfer, yet with comparable obstetric outcomes. None of these studies included placental analysis. STUDY DESIGN, SIZE, DURATION: A retrospective cohort study of 641 deliveries of IVF attained pregnancies between 2009 and 2017 was carried out. PARTICIPANTS/MATERIALS, SETTING, METHODS: Live singleton births after IVF with a single blastocyst transfer at a university-affiliated tertiary hospital were included. Excluded were cycles of oocyte recipients and IVM. We compared pregnancies following the transfer of a poor-quality blastocyst (poor-quality group) or a good-quality blastocyst (controls, good-quality group). During the study period, all placentas from complicated and uncomplicated pregnancies were sent to pathology. Primary outcomes were placental findings, including anatomic, inflammatory, vascular malperfusion, and villous maturation lesions, categorized according to the Amsterdam Placental Workshop Group Consensus. Secondary outcomes included obstetric and perinatal outcomes, adjusted for diminished ovarian reserve, fresh versus frozen transfer, and neonatal gender (as indicated by univariable analysis). MAIN RESULTS AND THE ROLE OF CHANCE: A total of 132 deliveries in the poor-quality group were compared to 509 controls. A diagnosis of diminished ovarian reserve was more common in the poor-quality group than in the control group (14.3% versus 5.5%, respectively, P  < 0.001) and more pregnancies in the poor-quality group were following frozen embryo transfer. After adjustment for confounders, poor-quality embryos were associated with a higher rate of low-lying placentas [adjusted odds ratio (aOR) 2.35, 95% CI 1.02–5.41, P  = 0.04] and placentas with a higher rate of villitis of unknown etiology (aOR 2.97, 95% CI 1.17–6.66, P  = 0.02), distal villous hypoplasia (aOR 3.78, 95% CI 1.20–11.38, P  = 0.02), intervillous thrombosis (aOR 2.41, 95% CI 1.39–4.16, P  = 0.001), multiple maternal malperfusion lesions (aOR 1.59, 95% CI 1.06–2.37, P  = 0.02), and parenchymal calcifications (aOR 2.19, 95% CI 1.07–4.46, P  = 0.03). LIMITATIONS, REASONS FOR CAUTION: The study is limited by its retrospective design and the utilization of two grading systems during the study period. In addition, the sample size was limited to detect differences in outcomes of rarer occurrences. WIDER IMPLICATIONS OF THE FINDINGS: The placental lesions demonstrated in our study imply an altered immunological response to the implantation of poor-quality embryos. Yet, these findings were not associated with additional adverse obstetric outcomes and merit reaffirmation in a larger cohort. Overall, the clinical findings of our study are reassuring to clinicians and patients for whom the transfer of a poor-quality embryo is necessary. STUDY FUNDING/COMPETING INTEREST(S): No external funding was obtained for this study. The authors declare no conflict of interest, TRIAL REGISTRATION NUMBER: N/A.